An experimental study on anode water management in high temperature PEM fuel cell. (13th April 2015) - Zhang, Caizhi; Zhou, Weijiang; Zhang, Lan; Chan, Siew Hwa; Wang, Youyi
Abstract An investigation into the effect of water in the anodic compartment on the performance of a high-temperature PBI-based PEM fuel cell (HT-PEMFC) has been carried out. This study shows that proper water management is as crucial to HT-PEMFCs as its low temperature (LT-PEMFC) counterpart. Excessive water content strongly affects the performance and stability of HT-PEMFCs. Here, a systemic study on the key parameters of anodic purging pressure, duration and frequency has been carried out in order to understand and propose a proper water management strategy for HT-PEMFCs. The results showed that proper programming of the anode purging process can effectively eliminate the serious water dilution effect in anode (similar to anodic flooding in LT-PEMFCs) and improve both the performance and fuel utilisation.